2018
DOI: 10.1002/jcp.27719
|View full text |Cite
|
Sign up to set email alerts
|

A2a adenosine receptor agonist improves endoplasmic reticulum stress in MIN6 cell line through protein kinase A/ protein kinase B/ Cyclic adenosine monophosphate response element‐binding protein/ and Growth Arrest And DNA‐Damage‐Inducible 34/ eukaryotic Initiation Factor 2α pathways

Abstract: Endoplasmic reticulum (ER) stress is one of the main molecular events underlying pancreatic beta cell (PBC) failure, apoptosis, and a decrease in insulin secretion. Recent studies have highlighted the fundamental role of A2a adenosine receptor (A2aR) in potentiation of insulin secretion and proliferation of PBCs. However, possible protective effects of A2aR signaling against ER stress have not been elucidated yet. Thus, in the present study, we aimed to investigate the effects of A2aR activation in MIN6 beta c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 62 publications
1
7
0
Order By: Relevance
“…These factors have been proven to play a vital role in wound healing, tumorigenesis, cell stemness and epithelial-mesenchymal transition, etc. For example, elF2a is involved in DNA damage repair and could regulate autophagy in tumors ( Arasi et al, 2019 ). elF3 family modulate of the hypoxia inducible factors (HIFs) and suppress tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…These factors have been proven to play a vital role in wound healing, tumorigenesis, cell stemness and epithelial-mesenchymal transition, etc. For example, elF2a is involved in DNA damage repair and could regulate autophagy in tumors ( Arasi et al, 2019 ). elF3 family modulate of the hypoxia inducible factors (HIFs) and suppress tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Although endogenous adenosine is accumulated during ischemia and is known to be an important mediator in innate protective pathways triggered by ischemic events, the effect of direct adenosine administration is limited by its short half-life and the simultaneous stimulation of all four adenosine receptor subtypes (A1, A 2a, A 2b , A3) [ 27 , 52 ]. Despite a significant overlap in the function of the receptors, most reports suggest that cAMP- and PKA-mediated protective and anti-inflammatory and anti-apoptotic effects are predominantly associated with the activation of the A 2a receptors [ 17 , 22 , 53 ], which underlines the importance of using a rather selective receptor stimulation. Previous molecular biological studies confirmed that the physiological and/or artificial stimulation of the adenosine A2a receptors induces the sequential activation of adenylate cyclase and protein kinase A (PKA) [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite a significant overlap in the function of the receptors, most reports suggest that cAMP- and PKA-mediated protective and anti-inflammatory and anti-apoptotic effects are predominantly associated with the activation of the A 2a receptors [ 17 , 22 , 53 ], which underlines the importance of using a rather selective receptor stimulation. Previous molecular biological studies confirmed that the physiological and/or artificial stimulation of the adenosine A2a receptors induces the sequential activation of adenylate cyclase and protein kinase A (PKA) [ 53 , 54 ]. The latter, by phosphorylating the adenosine A2a receptor, allows the G protein-mediated activation of phosphatidylinositol 3-kinase (PI3K).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some people have to quit their jobs because of their need for self-care [5]. Illness-related stress is a common reaction to DM [6,7]. There are many reasons for stress in people with diabetes, including, for example, conditions of the chronic disease, treatment received, lifestyle changes, economic situations, and changes in social roles.…”
Section: Introductionmentioning
confidence: 99%